Some Historical Information about the Life and Mathematical Heritage of Beruni - Farmonova M. O.; Sultanov J. S. (Research Parks Publishing LLC, 2020)
The article discusses materials about the life and mathematical heritage of the famous Central Asian scholar Abu Raikhan Beruni. Beruniy wrote his first major work at the age of 27 in Al-Asarul-bokiya (Remains of Ancient Peoples). In this work, the author reflects the achievements of scientists of that time in the field of mathematics, astronomy and geometry. Beruniy describes the ideas of the ancient Arabs, Iranians, Sogdians, Khorezmians, Greeks, Romans and other peoples cited in yearbooks, as well as information about popular months, weeks and days, holidays and traditions. Completed in 1031, Beruni's famous book, covering 80 chapters of “India,” is devoted to various aspects of astronomical science, as well as the development of geometry, history and other objects in Indian society, about Hindu religious beliefs and customs